Granulomatous Reactions from Tattoos Following BRAF Inhibitor Therapy - Giet, Gabrielle (Case Rep Dermatol, 2019)
BRAF inhibitors may present several cutaneous adverse effects, including actinic keratosis, squamous cell carcinoma, keratoacanthoma, rashes, increased photosensitivity, panniculitis, palmoplantar and capillary involvement, pruritus and xerosis as well as granulomatous reactions. A 30-year-old patient with multiple tattoos received dabrafenib and trametinib for metastatic melanoma. After 4 months, he developed an induration and thickening strictly limited to several tattoos. Histopathology revealed nonnecrotizing granulomas in the dermis. Topical steroids relieved pruritus but not the granulomatous aspect of the tattoos. As far as we know, this is the first description of granulomatous reactions restricted to preexisting tattoos following BRAF inhibitor therapy.